Effect of Climatic Factors and Habitat Characteristics on Anopheles Larval Density (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Koya Barat village is one of the areas in Jayapura City which has high incidence of malaria. Malaria cases in this region are affected by local conditions, including the climate and environment of aquatic habitats.The purpose of this study was to analyze the effect of climatic factors and habitat characteristics on Anopheleslarval density in Koya Barat village. The method used is field observation with descriptive and statistical analysis approach.The results showed that there are four parameters that significantly affect on larval density, namely rainfall, air temperature, water temperature and salinity. The relationship between rainfall with the larval density in freshwater permanent habitat is negative linear. While in brackish water permanent habitat and semi permanent habitat is non-linear (2nd order polynomial). The relationship between air temperature, water temperature and salinity with the larval density in freshwater habitat are positive linear, while in brackish water habitat and semi permanent habitat are negative linear.